Factors affecting conception rate on artificial insemination in goats - Remya Rajan V (Department of Animal Reproduction, College of Veterinary and Animal Sciences, 2010)
With the objective of evaluating the factors affecting conception rate on artificial insemination in goats, a study was carried out at Artificial Insemination Centre, under the department of Animal Reproduction, Gynaecology and Obstetrics, College of Veterinary and Animal Sciences, Mannuthy, Thrissur using 22 ejaculates collected thrice weekly from an adult Malabari crossbred buck. Semen samples for chilling were diluted in Tris-yolk buffer and preserved at 3-5oC for 72 hours. Cryopreservation was done in Tris yolk glycerol extender after the removal of seminal plasma. The semen was diluted and packed in 0.25 ml straws and each dose contained 200 million progressively motile sperms before processing.